Preservation of Digital and Conventional Archive To Information Rescue - Djoko Legowo; Marimin Marimin; Niken Fitriani; Ismiyati Ismiyati; Mar’atus Sholikah (Jurnal Scientia, 2024)
This research aims to identify and understand the implementation of conventional and digital archive preservation at the Unnes Archives UPT. This type of research is field research. Data collection techniques use observation, interviews and documentation. Research sampling used snowball sampling with three informants. The data analysis technique uses content analysis with the Miles, Huberman, and Saldana interactive model. The findings of this research are that the archives owned by UPT Archives Unnes consist of textual archives, photos, cartography, CDs (compact discs) and cassettes stored in conventional and digital media. Judging from the implementation of archive preservation, the relevant agencies have carried out their activities quite well, but digital archive preservation is still not optimal due to inadequate facilities, namely conventional files or archives that are transferred to digital media are unreadable or blurry, so the contents of the archive information cannot be known. In addition, pre-disaster prevention and recovery plans at the relevant agencies have not yet been planned. The agency does not yet have an evacuation route in the event of a disaster such as fire, earthquake and landslide. For this reason, relevant agencies are expected to be able to develop IT systems for managing digital archives and develop archive evacuation route strategies. Practically, these findings are useful for improving the implementation of archival preservation better and more optimally.